Sliding allows faster repositioning during tennis specific movements on hard court - Pavailler, S.; Horvais, N. (Procedia Engineering, 2014)
Tennis game is nowadays getting faster and players have to show strong defensive skills in order to win points. This implies returning more balls and repositioning very fast to get ready for the next stroke. In order to achieve this speed demand especially on hard court, a few players are able to slide like on clay court. The purpose of this study was to determine whether sliding on hard court allows a faster repositioning during a tennis specific routine. A total of eighteen male, national level tennis players participated in this study. A new concept of shoe (NSh) was developed specifically to allow players to slide on hard court. The subjects were asked to play three series of ten balls sent by a ball machine, once with the new shoe and once with a regular shoe (RSh). They were instructed to move back quickly to the centre of the court between each stroke. The players` displacements were videotaped (Casio Exilim FH25, Casio, Tokyo, Japan) at 120 Hz from a rear-view in order to record the centre of gravity (CG) trajectories. The main results showed that time for repositioning - defined as the time separating ball contact and CG movement direction inversion - was reduced by up to 42% when wearing NSh compared to RSh. This gain of time resulted in a 1.10 m shorter distance covered by the players between the hit of the ball and the repositioning at the centre of the court. These results are suggesting that with Nsh, the players were able to better adjust their body position to play the strokes. Instead of doing multiple little adjustment steps, players did large lunges, slid, and hit the ball in an open stance position, then began the repositioning right after the stroke.